Análise da produção bibliográfica dos professores da Escola de Veterinária da UFMG, no periodo de 1973 a 1977 - Campos, Carlita Maria (1980)
Analysis of the bibliographic production of the EV-UFMG faculty from 1973 to 1977, including journal papers, dissertations, theses, papers in proceedings of conferences, books, abstracts, etc. Two hunred and two journal papers, published during that time, were analyzed, and a mean of 2.1 papers per professor was found. Seven professors (29.61 por cento) were identified as the most productive. The periodical Arquivos da EV-UFMG publisehd 84.65 por cento of their papers (96.54 por cento) presented multiple authorship, most of them with four authors. Most papers were on animal production, with 4851 por cento on bovines. Also analyzed was the participation of 25EV-UFMG faculty in 34 of the 89 researches of "Projeto Bovinos". Analyzing the citations during that time, it was fiund a mean of 16.52 por cento citations per paper and various typer of documents, most of journal papers in English. American periodicals were the most cited, and Arquivos da EV-UFMG was the third most cited. The most popular periodical received 235 citations, but 205 periodicals were mentioned only once. It was found that 31.69 por cento of the references had only ones author. Among the references with more authors, the most common presented two. The publishing date varied from 1882 to 1977, with references with half life of 13-14 years. On hundred thirty four authors constituted the research front and were the most cited. Come collaboration eas found among the EV-UFMG faculty and other UFMG schools and reserches in other private and public organizations. The research busjects were related ot the departamental objevtives, to the interests of the veterinary community, and to the governmental priorities in this field.